PERSEPSI LANJUT USIA MENGENAI MENOPAUSE DI KECAMATAN REMBOKEN - Veronica Mandias; Kristamuliana; Maria Lupita Nena Meo (Universitas Sam Ratulangi, 2023)
Background: There will be various changes in the elderly both physical and psychological during aging process which can lead to various health issues. One of the physical changes is sexual function, namely the reproductive organs will experience changes because egg cells are no longer produced due to the cessation of menstruation. Aim: This study aimed to explore the perception of the elderly regarding menopause in Leleko village, Remboken sub-district. The Method used qualitative phenomenology with 7 main participants and 3 supporting participants, the data collection used in-depth interviews and observations. Result: based on interviews with all participants found 3 main themes, namely 1) Changes in various aspects of life before menopause, 2) Reaction to changes experienced and 3). The impression of the elderly about menopause. Conclusion: This study found that the elderly do not quite understand what menopause is, for that it is necessary to have education or counseling by health workers regarding what menopause is. For further researchers, they can use different methods other than phenomenological studies or the participants can be added. Keywords: Elderly; Menopause; Perception.